Desarrollo de una aplicación móvil educativa para el aprendizaje de tipos de ángulos en Educación General Básica Media - Muñoz Calderon, Jairo Manolo (2025)
The present study addresses the challenge of developing a technology that enhances performance in teaching and learning about the types of angles encountered in General Basic Secondary Education. The lack of interactive didactic resources for the area of mathematics, particularly regarding types of angles, is the problem that gives rise to this research. This study is developed under a technological design, which includes technological components in an educational Mobile App. Its total population consists of 90 students, of whom 30 were chosen from the mathematics area. A questionnaire consisting of five closed questions was applied to these students, who constitute the sample units. The methods included requirements analysis, design, implementation, testing, and installation. The results obtained from the implementation of the mobile software in one of the primary school groups last year indicate that the students have improved in their understanding and classification of angles. In summary, the instrument developed during this research serves as a tool to complement learning about angle classification in elementary school, offering an innovative educational experience aligned with the needs of the 21st century